Potential of digital applications for self-management and other outcomes in inflammatory rheumatic diseases: a systematic literature review - Volkmar, Alina; von der Decken, Cay-Benedict; Kleinert, Stefan; Karberg, Kirsten; Gauler, Georg; Klennert, Michael; Klennert, Jana; Aries, Peer Malte; Froschauer, Sonja; Wildenhain, Sarah; Muth, Theresia; Späthling-Mestekemper, Susanna; et al. (Frontiers in Medicine, 2025)
IntroductionInflammatory rheumatic diseases (IRDs) are chronic autoimmune conditions affecting the musculoskeletal system, leading to pain, disability, and reduced quality of life. Despite advances in medical treatments, barriers such as delayed diagnosis, workforce shortages, and low adherence to self-management strategies remain critical challenges. Digital health applications are emerging as promising tools to enhance disease management. The aim of this study was to conduct a systematic literature review (SLR) to evaluate self-care outcomes associated with digital health applications in IRDs.MethodsWe conducted a systematic literature review according to PRISMA guidelines across four electronic databases (PubMed, Embase, CINAHL, Cochrane) from inception to July 2024. Randomized controlled trials (RCTs) and systematic reviews focusing on digital interventions to promote self-management and self-care in individuals with IRDs were included. Key outcomes were extracted and the quality of the included studies was assessed using the Critical Appraisal Skills Programme (CASP) checklist.ResultsFifteen RCTs with a total of 1912 participants were analyzed. Primary outcomes, including self-management/self-care, showed mixed results. Some studies demonstrated significant improvements in self-efficacy, pain reduction, depression/anxiety symptoms, and physical function, while others showed no notable changes. Secondary outcomes, including disease activity and medication adherence, revealed heterogeneous findings. Variability in study design, sample size, and intervention duration posed challenges for drawing definitive conclusions about the effectiveness of digital interventions.DiscussionDigital health applications show promise as cost-effective and scalable solutions to complement standard IRD care by empowering patients in their disease management. However, significant heterogeneity and limited generalizability highlight the need for more robust and long-term research to validate the efficacy of specific tools and identify best options for improving outcomes. Tailored digital interventions could bridge the gap in care for IRD patients and support their autonomy.